An Investigation into the Assessment of Critical Thinking Skills in Physics Textbooks for Grade X Semester II at Senior High Schools - Miftahurrahmi Miftahurrahmi; Fanny Rahmatina Rahim; Fanny Rahmatina Rahim; Gusnedi Gusnedi; Gusnedi Gusnedi; Silvi Yulia Sari; Silvi Yulia Sari (Universitas Lambung Mangkurat, 2024)
In the context of the revised 2013 curriculum, critical thinking skills have become essential for students in the 21st century. A survey conducted across public high schools in Padang revealed that various sources authored and published physics textbooks used by these schools. However, it remains unclear whether these printed books incorporate indicators of critical thinking skills. Consequently, researchers analyzed the Higher Order Thinking Skills (HOTS) component, explicitly focusing on critical thinking, in physics textbooks used in high schools. This descriptive study employed a mixed-methods approach, combining quantitative and qualitative analysis. The study population consisted of all Grade X Semester II physics textbooks across 16 public high schools in Padang. The sample comprised widely used printed books from three publishers: Intan Pariwara's 2016 physics textbook, Erlangga's 2016 publication, and Tiga Serangkai's 2016 printed book. Research data were collected using an analysis instrument for HOTS indicators in Grade X Semester II physics textbooks. Findings indicate that the ER book exhibited the highest availability of critical thinking skills indicators within the